Гемореологические аспекты метаболизма оксида азота в эритроцитах при развитии сосудистой дисфункции - Рамазанов, В.В.; Воловельська, Є.Л.; Ніпот, О.Є.; Єршов, С.С.; Єршова, Н.А.; Руденко, С.В.; Бондаренко, В.А. (Український журнал медицини, біології та спорту, 2018, т. 3, № 6 (15), стр. 262-268, 2018)
Метаболизм эритроцитов является составной частью гомеостаза организма, и во многом отражает изменения, которые происходят в органах и тканях при различных заболеваниях. Однако нарушение системной функции эритроцитов, связанной с окислительным стрессом и изменением гемореологических свойств, может вызвать нарушение гемодинамики и развитие сосудистой дисфункции. Представленные в обзоре данные литературы указывают на то, что некоторые статины и вазодилататоры обладают многовекторным воздействием, включая противовоспалительное и антиоксидантное, а также способны корректировать метаболизм оксида азота и гемореологические свойства эритроцитов. Поэтому разработка новых терапевтических стратегий лечения сосудистых осложнений может быть основана на использовании комбинаций указанных препаратов и лекарственных средств, которые являются донорами оксида азота и способствуют нитрозилированию гемоглобина и белков цитоскелета. -----------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------Метаболізм еритроцитів є складовою частиною гомеостазу організму і багато в чому відображає зміни, які відбуваються в органах і тканинах при різних захворюваннях. Однак порушення системної функції еритроцитів, пов'язаної з окислювальним стресом і зміною гемореологических властивостей, може викликати порушення гемодинаміки і розвиток судинної дисфункції. Представлені в огляді дані літератури вказують на те, що деякі статини і вазодилататори мають багатовекторним впливом, включаючи протизапальну і антиоксидантну і здатні коригувати метаболізм оксиду азоту і гемореологічні властивості еритроцитів. Тому розробка нових терапевтичних стратегій для лікування судинних ускладнень, може бути заснована на використанні комбінацій зазначених препаратів і лікарських засобів, які є донорами оксиду азоту і сприяють нітрозіліруванію гемоглобіну і білків цитоскелету. ---------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------The development of vascular dysfunction with age and with various diseases is associated with the accumulation of a joint effect of oxidative stress and inflammation on the vascular walls. At the same time, the viscosity of the blood and the shear stress of the flow on the vessel walls are due to the hemorheological properties of the red blood cells, which to a certain extent depend on the metabolism of nitric oxide (NO). Metabolism of erythrocytes is the subject of homeostatic regulation and reflects the changes that occur in organs and tissues in various diseases. The ability of erythrocytes to restore extracellular antioxidants during overproduction of vascular oxidants is their ideal component of the system of redox-balance of the body. At the same time, oxidative stress, changes in the metabolism of nitric oxide and haemorheological properties of red blood cells can lead to a violation of hemodynamics and accelerate the development of vasopathology. Decrease in deformability and increase in erythrocyte aggregation is noted when they are aging in a healthy body, but more pronounced in various diseases including cardiovascular, which determines a violation of microcirculation and systemic hemodynamics. In this case it is logical to raise the question whether correction of erythrocytes rheological disturbances, connected with NO metabolism, can prevent the development of vascular complications. Analysis of literature data indicates that red blood cells play an important role in regulating arterial pressure and tissue perfusion due to production, accumulation and release of nitric oxide via nitrosothiols, nitrosohemoglobin and protene-disulfide isomerase. However, erythrocyte dysfunction associated with oxidative stress, changes in NO metabolism and hemorheological properties in various diseases is noted, which in sum causes an acceleration in the development of vascular pathology. In the microcirculation system, the hypoxic conditions and the effect of mechanical stress on erythrocytes stimulate NO production due to the nitrite-reductase activity of deoxy-Hb, which makes a significant contribution to vasodilation. Nitrite-reductase activity of deoxy-Hb can serve a compensatory mechanism for correcting microcirculatory hemodynamics in cardiovascular diseases and peripheral vascular diseases. Probably, the metabolism and bioavailability of nitric oxide in erythrocytes can largely determine systemic hemodynamics both in norm and in pathology. Development of a new therapeutic strategy for the treatment of patients with microvascular complications can be associated with the use of NOdonors (morpholinosidonimine, peroxynitrite, nitroprusside), which improve the erythrocyte deformability, promote the formation of nitrosothiols and nitrosohemoglobin. In addition, some drugs have a wide range of action and can be used in the development of this strategy (rosuvastatin, pentoxifylline, dipyridamole). These drugs stimulate the production of NO in endotheliocytes and erythrocytes and have a multivector effect, including hemorheological, anti-inflammatory and antioxidant. This can reveal new opportunities for treating various diseases, which are accompanied by vascular dysfunction and hemodynamic disorders. The literature data presented in the review indicate that red blood cells are target cells of the effect of certain drugs that are capable of correcting the metabolism of nitric oxide and haemorheological properties, which probably contributes to the prevention of vascular dysfunction. Conclusion. Therefore, the development of new therapeutic strategies for treatment of vascular complications can be based on the use of combinations of these drugs and drugs that are donors of nitric oxide and promote nitrosylation of hemoglobin and cytoskeleton proteins.
Hemoreological Aspects of Nitric Oxide Metabolism in Erythrocytes at Development of Vascular Dysfunction
Рамазанов ВВ, Воловельская ЕЛ, Нипот ЕЕ, Ершов СС, Ершова НА, Руденко СВ, Бондаренко ВА. Гемореологические аспекты метаболизма оксида азота в эритроцитах при развитии сосудистой дисфункции. Український журнал медицини, біології та спорту. 2018; 3(6):262-8
Keywords: эритроциты; сосудистые дисфункции; оксид азота; гемореология